An Uncertain Future for Afghanistan's Security Sector. Issue 1 (14th November 2014) - Sedra, Mark
Western powers may have espoused accountability, civil society, and good governance, but their Afghan operations have largely emphasized training and equipping for security. Military capacities are higher now but those forces are not necessarily balanced, well-managed, or sustainable. A paramilitarized police has alienated communities. Ministries of Defense and Interior are imperiled by lacks in planning, civilian oversight, and budget sufficiency. To stabilize gains of the last decade, donors need to renew their commitments to major (but more discerning) assistance.